Diversity of epothilone producers among Sorangium strains in producer‐positive soil habitats. Issue 2 (6th December 2013) - Li, Shu‐guang; Zhao, Lin; Han, Kui; Li, Peng‐fei; Li, Zhi‐feng; Hu, Wei; Liu, Hong; Wu, Zhi‐hong; Li, Yue‐zhong
Summary Large‐scale surveys show that the anti‐tumour compounds known as epothilones are produced by only a small proportion of Sorangium strains, thereby greatly hampering the research and development of these valuable compounds. In this study, to investigate the niche diversity of epothilone‐producing Sorangium strains, we re‐surveyed four soil samples where epothilone producers were previously found. Compared with the < 2.5% positive strains collected from different places, epothilone producers comprised 25.0–75.0% of the Sorangium isolates in these four positive soil samples. These sympatric epothilone producers differed not only in their 16S rRNA gene sequences and morphologies but also in their production of epothilones and biosynthesis genes. A further exploration of 14 soil samples collected from a larger area around a positive site showed a similar high positive ratio of epothilone producers among the Sorangium isolates. The present results suggest that, in an area containing epothilone producers, the long‐term genetic variations and refinements resulting from selective pressure form a large reservoir of epothilone‐producing Sorangium strains with diverse genetic compositions.